Health information science : Third International Conference, HIS 2014, Shenzhen, China, April 22-23, 2014. Proceedings - Yao, Guiqing; He, Jing; Wang, Lei; Smalheiser, Neil R.; Yin, Xiaoxia; Zhang, Yanchun (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the Third International Conference on Health Information Science, HIS 2014, held in Shenzhen, China, in April 2014. The 29 full papers presented were carefully reviewed and selected from 61 submissions. They cover a wide range of topics in health information sciences and systems that support the health information management and health service delivery. They deal with medical/health/biomedicine information resources, such as patient medical records, devices and equipments, software and tools to capture, store, retrieve, process, analyse, and optimize the use of information in the health domain; data management, data mining, and knowledge discovery, all of which play a key role in the decision making, management of public health, examination of standards, privacy and security issues; computer visualization and artificial intelligence for computer-aided diagnosis; and development of new architectures and applications for health information systems.